Analisis Pengaruh Tingkat Pendidikan dan Pertumbuhan Penduduk terhadap Pertumbuhan Ekonomi di Indonesia periode 2017-2021 - Aulia Hassanah (Journal of Management and Social Sciences, 2022)
This study aims to analyze the effect of education level and population growth on economic growth in Indonesia for the 2017-2021 period. Economic growth is a process of changing economic conditions that occur in a country on an ongoing basis towards a condition that is considered better for a certain period of time. This research is a quantitative study, the data was processed using panel data analysis consisting of cross sectional data from six provinces and time series data for 2017-2021. The best regression model in this research data is the FEM (Fixed Effect Model) regression model. The results of this study show that simultaneously the variables of Education Level and Population Growth have no effect and are not significant on Economic Growth in Indonesia for the 2017-2021 period. And partially the variables of Education Level and Population Growth have no effect and are not significant on Economic Growth in Indonesia for the 2017-2021 period.